Crop Diversification among Rural Farm Households in Kwande Local Government Area of Benue State, Nigeria - Nyiatagher, Z. T.; Abiyong, P. A.; Aniah, N. U. (International Journal of Environment, Agriculture and Biotechnology, 2019)
This study analysed crop diversification among rural farm households in Kwande Local Government Area of Benue State, Nigeria. The study drew a sample of 360 rural farm households through a multi-stage sampling technique from 12 communities in four districts of Kwande LGA (Ikyurav-ya, Turan, Nanev and Shangev-ya) and the primary data obtained were analysed using the descriptive statistics, Simpson index and Tobit regression model. Results indicated that an average farm household head was 42.8 years old and had 4.2 years of schooling. Ninety three percent (93 %) of the farm households diversified their cropping activities with 51.7 percent diversified into three or more crops. The Tobit regression results revealed that there were marginal increases in crop diversification with increase in farm size, gender, access to credit, membership of co-operative and educational level but crop diversification decreases as farmers grow older in age and farming experience. Policy implications were drawn for provision of functional social amenities and encouragement of the rural farmers to join cooperative societies for easy access to loans that promote crop diversification and hence improve the standard of living of the rural populace